Lateral Meniscal Graft Transplantation: Effect of Fixation Method on Joint Contact Mechanics During Simulated Gait. Issue 10 (August 2019) - Brial, Caroline; McCarthy, Moira; Adebayo, Olufunmilayo; Wang, Hongsheng; Chen, Tony; Warren, Russell; Maher, Suzanne
Background: Controversy exists regarding the optimal bony fixation technique for lateral meniscal allografts. Purpose/Hypothesis: The objective was to quantify knee joint contact mechanics across the lateral plateau for keyhole and bone plug meniscal allograft transplant fixation techniques throughout simulated gait. It was hypothesized that both methods of fixation would improve contact mechanics relative to the meniscectomized condition, while keyhole fixation would restore the distribution of contact stress closer to that of the intact knee. Study Design: Controlled laboratory study. Methods: Six human cadaveric knees were mounted on a multidirectional dynamic simulator and subjected to the following conditions: (1) native intact meniscus, (2) keyhole fixation of the native meniscus, (3) bone plug fixation of the native meniscus, and (4) meniscectomy. Contact area, peak contact stress, and the distribution of stress across the tibial plateau were computed at 14% and 45% of the gait cycle, at which axial forces are at their highest. Translation of the weighted center of contact stress throughout simulated gait was computed. Results: Both bony fixation techniques improved contact mechanics relative to the meniscectomized condition. The keyhole technique was not significantly different from the intact condition for the following metrics: contact area, peak contact stress, distribution of force between the meniscal footprint and cartilage-to-cartilage contact, and the position of the weighted center of contact. In contrast, bone plug fixation resulted in a significant decrease of 21% to 28% in contact area at 14% and 45% of the simulated gait cycle, a significant increase in peak contact stresses of 34% at 45% of the gait cycle, and a shift in the weighted center of contact, which increased forces in the cartilage-to-cartilage contact area at 45% of the gait cycle. Conclusion: While both keyhole and bone plug fixation methods improved lateral compartment contact mechanics relative to the meniscectomized knee, keyhole fixation restored contact mechanics closer to that of the intact knee. Clinical Relevance: Method of meniscal fixation is under the direct control of the surgeon. From a biomechanics perspective, keyhole fixation is advocated for its ability to mimic intact knee joint contact mechanics.